Limitations of the Personalization of Marketing Tools - Baran, Radosław (Studia Oeconomica Posnaniensia, 2018)
The paper discusses the issue of limitations of the personalization of marketing tools. The aim of this paper is to identify and to describe these limitations and is based on the analysis of the secondary sources. In some cases the personalization of marketing tools is not beneficial for a company. Some authors describe certain selected factors which are unfavorable for making use of this personalization. The author presents a comprehensive approach to the issue of limitations of personalization of marketing tools. Several main limitations have been identified and these limitations concern legal factors, technological factors, buyers behavior, the features of products, and also a company's resources and competences.